2019
DOI: 10.1038/s41419-019-1950-1
|View full text |Cite
|
Sign up to set email alerts
|

The pharmalogical reactivation of p53 function improves breast tumor cell lysis by granzyme B and NK cells through induction of autophagy

Abstract: Cytotoxic T lymphocytes (CTL) and natural killer cells (NK)-mediated elimination of tumor cells is mostly dependent on Granzyme B apoptotic pathway, which is regulated by the wild type (wt) p53 protein. Because TP53 inactivating mutations, frequently found in human tumors, could interfere with Granzyme B-mediated cell death, the use of small molecules developed to reactivate wtp53 function in p53-mutated tumor cells could optimize their lysis by CTL or NK cells. Here, we show that the pharmalogical reactivatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 62 publications
0
30
1
Order By: Relevance
“…In cancer, a mutated p 53 decreases autophagy and favors the proliferation of tumoral cells, and thus it could be a therapeutic target. In autophagy, anti-apoptotic proteins, such as Bcl-xL and XIAP are also degraded, thus promoting the removal of tumor cells by cytotoxic lymphocytes and NK cells through the Granzyme pathway [ 86 ]. In fact, p53 activates autophagy; conversely, autophagy suppresses the expression of p53, thus promoting cancer proliferation [ 87 ].…”
Section: Pathways and Molecular Mechanisms Of Autophagymentioning
confidence: 99%
“…In cancer, a mutated p 53 decreases autophagy and favors the proliferation of tumoral cells, and thus it could be a therapeutic target. In autophagy, anti-apoptotic proteins, such as Bcl-xL and XIAP are also degraded, thus promoting the removal of tumor cells by cytotoxic lymphocytes and NK cells through the Granzyme pathway [ 86 ]. In fact, p53 activates autophagy; conversely, autophagy suppresses the expression of p53, thus promoting cancer proliferation [ 87 ].…”
Section: Pathways and Molecular Mechanisms Of Autophagymentioning
confidence: 99%
“…Breast cancer cells in hypoxic conditions were able to evade NK cell killing via the activation of autophagy and the subsequent degradation of granzyme B in vitro [102]. However, in non-hypoxic conditions restoration of p53 function in breast cancer cells increased their susceptibility to NK cell cytotoxicity via autophagic sequestering of antiapoptotic Bcl-2 family members, which potentiated granzyme B-induced apoptosis [103]. It is important to determine the effect of autophagy on tumour cell susceptibility to NK cell cytotoxicity in vivo as differences in the TME could alter the ability of autophagy to inhibit/enhance NK cell-induced apoptosis in tumour cells.…”
Section: Protection From Innate Immune Cell Killingmentioning
confidence: 99%
“…With the expression of nuclear p53 stimulated by starvation conditions, the activated AMPK induces autophagy through the TSC1/TSC2 complex and mTOR pathway ( Figure 4 ) ( Hu et al, 2019 ; Gao et al, 2020 ). Chollat-Namy et al (2019) have found that p53 upregulates the expression of its downstream targets Sestrin-1 and Sestrin-2, which further activate AMPK through phosphorylating AMPK at Thr172, subsequently leading to the dephosphorylation of mTORC1 at S2448 and the induction of autophagy. Damage-regulated autophagy modulator (DRAM) and death-associated protein kinase 1 (DAPK1) are other important downstream targets of p53 and have been reported to induce autophagy ( Crighton et al, 2006 ; Zhou et al, 2016 ; Hu et al, 2019 ).…”
Section: Overview Of Autophagymentioning
confidence: 99%